2015
DOI: 10.3109/02813432.2015.1118836
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ attitudes toward follow-up after cancer treatment: A cross-sectional questionnaire study

Abstract: Objective An increasing number of cancer patients place a significant workload on hospital outpatient clinics, and health authorities are considering alternative follow-up regimens. It has been suggested that follow-up of cancer patients could be provided by GPs. This study aimed to explore GPs’ experiences with the provision of follow-up care for cancer patients, and their views on assuming greater responsibility in the future.Design Electronic questionnaire study.Subjects GPs in seven regions in Norway.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 17 publications
2
41
2
Order By: Relevance
“…[12][13][14]21,22 However, according to previous studies, not only do GPs feel competent to provide this kind of follow-up care, they regard themselves as better suited than specialists to provide psychosocial support to cancer patients. 5,23 Contrary to our findings, cross-sectional studies of patients with breast, prostate and melanoma cancer have shown that these patients prefer to see their GP for psychosocial matters and general care. 13,24,25 The patients in our study thought that the main reason for attending follow-up is to detect possible recurrence, which is in line with most previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[12][13][14]21,22 However, according to previous studies, not only do GPs feel competent to provide this kind of follow-up care, they regard themselves as better suited than specialists to provide psychosocial support to cancer patients. 5,23 Contrary to our findings, cross-sectional studies of patients with breast, prostate and melanoma cancer have shown that these patients prefer to see their GP for psychosocial matters and general care. 13,24,25 The patients in our study thought that the main reason for attending follow-up is to detect possible recurrence, which is in line with most previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The preference of a specialist may also be founded on a belief that GPs have limited abilities to perform cancer‐specific follow‐up care . However, according to previous studies, not only do GPs feel competent to provide this kind of follow‐up care, they regard themselves as better suited than specialists to provide psychosocial support to cancer patients . Contrary to our findings, cross‐sectional studies of patients with breast, prostate and melanoma cancer have shown that these patients prefer to see their GP for psychosocial matters and general care .…”
Section: Discussioncontrasting
confidence: 73%
“…15 Studies have variously used questionnaires and surveys to explore patients' and GPs' perspectives on follow-up care of cancer in primary care. [16][17][18][19] Murchie et al conducted semi-structured interviews to understand the practical experiences of GPs in GP-led melanoma follow-up. 11 In our study, we used a survey to collect information about skin cancer follow-up practices in regional Victoria and explore the challenges in the follow-up, and interviews to collect in-depth information about the practices and challenges.…”
Section: Discussionmentioning
confidence: 99%
“…18 19 The results of an Australian randomised control trial examining integrated care with hospitals and general practitioners (GPs) for patients with prostate cancer also demonstrated that this was a safe and acceptable model of care at lower cost to the healthcare system. 20 GPs feel confident and enabled to contribute to long-term cancer care 21 and cancer survivors are satisfied with care delivery in primary care. 22 There have been a number of studies examining follow-up of lung cancer in different settings.…”
Section: Introductionmentioning
confidence: 99%
“…26 The potential shift in the care for patient with cancer with greater GP involvement also raises concerns that GP workloads may be increased. 21 There is additional concern that perhaps GPs will see very few of these cases in their practice and thus may not be adequately confident or have sufficient experience to safely follow-up these patients. 15 27 The proposed solution in this situation would be the use of a protocol in conjunction with clinical acumen to guide follow-up.…”
Section: Introductionmentioning
confidence: 99%